Influence of elektromagnetics vibrations refraction index to pseudodistance accuracy in GPS measurements - Skeivalas, Jonas (Geodesy and Cartography, 2012)
Research demonstrates the accuracy of pseudo distance measurements evaluating the impact of the refraction index and spread speed of vibrations in the vacuum. It also shows the influence of the refraction index of vibrations and spread speed errors to the errors of pseudo distances. Establishing the refraction index of vibrations has the major impact on the accuracy of pseudo distances performing GPS measurements. The limited possibilities of evaluating the measurements of atmosphere parameters and marked fluctuations in values define the estimation errors of the refraction index of vibrations. The influence of establishing errors in vibration speed in the vacuum on errors occurring in pseudo distances is expressed at a much lower row (level). The article presents the equations for evaluating the refraction index of vibrations and the measured accuracy of pseudo distances depending on the known accuracy of the values of atmospheric parameters. Article in Lithuanian. Elektromagnetinių virpesių lūžio rodiklio įtaka pseudoatstumų tikslumui atliekant GPS matavimus Santrauka. Straipsnyje nagrinėjamas pseudoatstumų matavimo tikslumas, įvertinant virpesių lūžio rodiklio bei virpesių sklidimo greičio vakuume įtaką. Tai pasireiškia virpesių lūžio rodiklio bei jų sklidimo greičio klaidų įtaka matuojamų pseudoatstumų klaidoms. Pseudoatstumų tikslumui, atliekant GPS matavimus, daugiausiai įtakos turi virpesių lūžio rodiklio nustatymo tikslumas. Virpesių lūžio rodiklio nustatymo klaidas apibrėžia ribotos atmosferos parametrų reikšmių matavimo tikslumo galimybės bei žymios šių reikšmių fliuktuacijos. Virpesių greičio vakuume nustatymo klaidų įtaka pseudoatstumų klaidoms pasireiškia žymiai mažesne eile (lygiu). Darbe pateikiamos formulės virpesių lūžio rodiklio bei išmatuotų pseudoatstumų tikslumui įvertinti priklausomai nuo žinomo atmosferos parametrų reikšmių tikslumo. Reikšminiai žodžiai: virpesių lūžio rodiklis, GPS, kovariacija, pseudoatstumai. First published online: 03 Aug 2012